Current Trends of the Incidence and Pathological Diagnosis of Gastroenteropancreatic Neuroendocrine Tumors (GEP-NETs) in Korea 2000-2009: Multicenter Study - Cho, Mee-Yon; Kim, Joon Mee; Sohn, Jin Hee; Kim, Mi-Jung; Kim, Kyoung-Mee; Kim, Woo Ho; Kim, Hyunki; Kook, Myeong-Cherl; Park, Do Youn; Lee, Jae Hyuk; Chang, HeeKyung; Jung, Eun Sun; et al. (Cancer research and treatment, 2012)
As a result of various independently proposed nomenclatures and classifications, there is confusion in the diagnosis and prediction of biological behavior of gastroenteropancreatic neuroendocrine tumors (GEP-NETs). A comprehensive nationwide study is needed in order to understand the biological characteristics of GEP-NETs in Korea. We collected 4,951 pathology reports from 29 hospitals in Korea between 2000 and 2009. Kaplan-Meier survival analysis was used to determine the prognostic significance of clinicopathological parameters. Although the GEP-NET is a relatively rare tumor in Korea, its incidence has increased during the last decade, with the most significant increase found in the rectum. The 10-year survival rate for well-differentiated endocrine tumor was 92.89%, in contrast to 85.74% in well differentiated neuroendocrine carcinoma and 34.59% in poorly differentiated neuroendocrine carcinoma. Disease related death was most common in the biliary tract (62.2%) and very rare in the rectum (5.2%). In Kaplan-Meier survival analysis, tumor location, histological classification, extent, size, mitosis, Ki-67 labeling index, synaptophysin expression, lymphovascular invasion, perineural invasion, and lymph node metastasis showed prognostic significance (p<0.05), however, chromogranin expression did not (p=0.148). The 2000 and 2010 World Health Organization (WHO) classification proposals were useful for prediction of the prognosis of GEP-NET. The incidence of GEP-NET in Korea has shown a remarkable increase during the last decade, however, the distribution of tumors in the digestive system differs from that of western reports. Assessment of pathological parameters, including immunostaining, is crucial in understanding biological behavior of the tumor as well as predicting prognosis of patients with GEP-NET.